Effects of electrospraying parameters on deposition of La0.3Sr0.7Fe0.7Cr0.3O3-? cathode layer on GDC - Akkurt, Sedat; Sindirac, Can; Egesoy, Tugce Ozmen; Atici, Gokce; Erisman, Elif; Ergen, Emre; Büyükaksoy, Aligül (Wiley, 2023)
High performance in intermediate temperature solid oxide fuel cells requires improvements especially in the microstructure of the cathode layer. New cobalt-free cathode materials are used because cobalt-containing cathodes have higher thermal expansion coefficients, poor long-term chemical stability, and lower mechanical stability. Recently cobalt-free cathodes have been proposed to solve these issues by using deposition methods other than electrospray deposition (ESD). In this study, ESD method is used to develop a cobalt-free cathode layer. The electrolyte layer is gadolinium-doped ceria that is deposited with La0.3Sr0.7Fe0.7 Cr0.3O3-delta (LSFCr) prepared by 2-butoxyethanol and ethylene glycol solvents as opposed to conventional solvents. Experimental ESD parameters are tested at different levels and combinations by applying statistical experimental design methods to optimize the microstructure. Coating deposited as such demonstrated higher electrochemical performance than similar electrodes fabricated by other methods.
Keywords: ESD; fuel cell cathode; LSFCr; SOEC; SOFC; statistical experimental design